2020
DOI: 10.3389/fnins.2020.574652
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide for the Treatment of Parkinson Disease: A Current Update

Abstract: Zonisamide has been used as an add-on treatment in order to overcome the deficiencies of the general therapies currently used to resolve the motor complications and non-motor symptoms of Parkinson disease. Various trials have been designed to investigate the mechanism of action and treatment effects of zonisamide in this condition. Most clinical trials of zonisamide in Parkinson disease were from Japan. The vast majority of studies used changes in the Unified Parkinson’s Disease Rating Scale (UPDRS) scores and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 98 publications
(160 reference statements)
0
20
0
1
Order By: Relevance
“…Pregabalin was approved for generalized anxiety disorder in the European Union in 2006 [ 121 ]. Furthermore, based on randomized controlled trials, zonisamide is considered a safe and efficacious add-on treatment in Parkinson‘s disease [ 123 ], whereas no robust efficacy was reported for topiramate or levetiracetam [ 124 ]. Preliminary clinical data indicated that cannabidiol improved quality of life but not motor symptoms in patients with Parkinson’s disease [ 125 ], and larger randomized controlled trials are ongoing [ 124 ].…”
Section: Use Of Antiseizure Medications For Nonepileptic Conditionsmentioning
confidence: 99%
“…Pregabalin was approved for generalized anxiety disorder in the European Union in 2006 [ 121 ]. Furthermore, based on randomized controlled trials, zonisamide is considered a safe and efficacious add-on treatment in Parkinson‘s disease [ 123 ], whereas no robust efficacy was reported for topiramate or levetiracetam [ 124 ]. Preliminary clinical data indicated that cannabidiol improved quality of life but not motor symptoms in patients with Parkinson’s disease [ 125 ], and larger randomized controlled trials are ongoing [ 124 ].…”
Section: Use Of Antiseizure Medications For Nonepileptic Conditionsmentioning
confidence: 99%
“…However, a number of compounds able to increase KYNA levels, through mechanisms distinct from interference with KP, successfully ameliorated L‐DOPA–induced dyskinesias. One of the interesting therapeutic options for PD seems to be the antiepileptic drug zonisamide, shown to reduce motor symptoms in patients with L‐DOPA–induced dyskinesias 215 . Zonisamide, apart from his broad pharmacological effects including inhibition of voltage‐gated sodium channels, T‐type calcium channels, and monoamine‐oxidase, has been shown to increase KYNA production 216 .…”
Section: Therapeutic Perspectives Of Increasing Kyna Levels In Neurodegenerative Disordersmentioning
confidence: 99%
“…The antiparkinsonian effects of ZNS have been reported in our previous studies on MPTP and in a 6-OHDA-treated animal model of PD, where we found that ZNS acts as a neuroprotectant against MPTP-induced dopaminergic neuronal degeneration by acting directly on neurones and astrocytes [ 14 , 15 , 16 , 17 ]. In addition to our studies, several research studies published by different groups have highlighted the antiparkinsonian effects of ZNS [ 33 ]. A study showed that ZNS reduced neuroinflammation by inhibiting Nav1.6 and TNFα in microglial cells in an MPTP-treated mouse model of PD.…”
Section: Discussionmentioning
confidence: 77%